Case Report: Diagnostic itinerary of a male case of juvenile-onset systemic lupus erythematosus in Bouake - Traore, Aissata Doucoure; Koffi, Joseph Kan Enock; Koffi, Christ Ziahy Reine Marie; Yao, Konan Joe Clovis; Goua, Jean Jacque; Kouakou, Ehaulier Soh Christian; Tia, Weu Melanie; Daboiko, Felix Jean Claude (Frontiers in Pediatrics, 2025)
Juvenile-onset systemic lupus erythematosus (JLES) is an autoimmune disease of unknown aetiology. It is more common in girls but can occur in boys. Its onset at an early age is more severe, causing potentially fatal damage if not treated early. It is a polymorphous condition, misleading at first and little known in our African populations. We report a case of 12 years of misdiagnosis in a 17-year-old boy living in a semi-rural environment. This case illustrates the shortage of paediatric rheumatologists and marks a breaking point in the diagnosis of the disease, which is sometimes difficult even for practitioners, making it difficult for sick children to access care. It is important to make the general public, as well as nurses and doctors, aware of the importance of early diagnosis for effective and efficient treatment.